PERAMALAN PENYEBARAN JUMLAH KASUS VIRUS EBOLA DI GUINEA DENGAN METODE ARIMA - Novita Eka Chandra; Sarinem Sarinem (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2016)
Ebola virus can cause death. The spread number of cases of this virus is very rapidly, especially in the Guinea of West Africa. Based on the past data, the spread number of cases of ebola virus can be predicted by the method of time series namely ARIMA method. In this study the researcher used 63 cases of ebola virus. By using ARIMA method, it was found that an appropriate model for the spread of ebola virus cases is ARIMA(0,2,3). Based on the model, the spread number of cases of ebola virus can be predictedfor the next 13 periods, with the result that the spread number of cases of ebola virus has decreased from period to period.